General Integral Control - Bai-shun Liu; Bing-Li Tian (2009 International Conference on Advanced Computer Control, 2009)
In this paper we overcome the restriction of conventional integrators and present a unified framework for general integral control (GIC). The necessary conditions and basic principles for designing a general integrator are proposed. All asymptotically stable controllers in conjunction with the limited conditions described can be directly used as integrators and all techniques for designing these controllers can be used to design a general integrator and analyze its stability. Many control laws can easily be transformed into GIC laws and many control theories can be used to design a GIC controller, analyze its stability and tune its parameters. Theoretical analysis and simulation results demonstrated that the general integrator has stronger capability, faster convergence and better flexibility than previous integrators and the windup phenomenon can be eliminated. Moreover, compared to previous integral control, GIC can remarkably improve transient performance by using the same maximum control action.